Pemberian Produk Olahan Berbasis Sumber Besi (Fe) terhadap Kadar Hemoglobin Ibu Hamil - Suryani Suryani; Neni Heryani; Atika Fadhilah Danaz Nasution (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the effect of providing processed products based on iron (Fe) sources on hemoglobin levels in pregnant women in the work area of Penyengat Olak Health Center, Muaro Jambi Regency. The design used in this study was a quasi-experimental design using the One Group pretest-posttest design. The results showed that most mothers were 20-35 years old (86.7%), the majority were mothers with multigravida (60%). The average hemoglobin level before giving processed food was 10.383 gr%. The intermediate hemoglobin level after giving processed food was 11,903 gr%. In conclusion, there is an effect of providing processed food based on iron (Fe) sources in the work area of the Penyengat Olak Health Center, Muaro Jambi Regency, in 2020. Keywords: Haemoglobin, Pregnancy, Food, Iron